2005
DOI: 10.1021/es049214x
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic Ecological Risk Assessment of 1,2,4-Trichlorobenzene at a Former Industrial Contaminated Site

Abstract: Measured concentrations of 1,2,4-trichlorobenzene (1,2,4-TCB) in soil and groundwater detected in an industrial contaminated site were used to test several probabilistic options for refining site-specific ecological risks assessment, ranging from comparison of single effects and exposure values through comparison of probabilistic distributions for exposure and effects to the use of distribution based quotients (DBQs) obtained through Monte Carlo simulations. The results of the deterministic approach, which sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 101 publications
(49 citation statements)
references
References 26 publications
0
48
0
1
Order By: Relevance
“…The risk assessment process used in this study was a tiered approach following published methods (ECOFRAM 1999;Zolezzi et al 2005;Wang et al 2009) and consisting on four levels-deterministic, etc.…”
Section: Tiered Risk Characterizationmentioning
confidence: 99%
See 4 more Smart Citations
“…The risk assessment process used in this study was a tiered approach following published methods (ECOFRAM 1999;Zolezzi et al 2005;Wang et al 2009) and consisting on four levels-deterministic, etc.…”
Section: Tiered Risk Characterizationmentioning
confidence: 99%
“…Margins of safety greater than 1.0 indicated that the distributions did not overlap and thus minimal risk to aquatic organisms. In addition, the exceedance probability function (EXF, calculated as 100-cumulative distribution function) and the SSD were used to generate a joint probability curve (JPC), which describes the probability of a particular set of exposure conditions occurring relative to the number of taxa that would be affected (Solomon et al 2000;Zolezzi et al 2005;Wang et al 2009). …”
Section: Tiered Risk Characterizationmentioning
confidence: 99%
See 3 more Smart Citations